Nonsteroidal anti-inflammatory drugs: problems of safe use - N. Yu. Velts; E. O. Zhuravleva; T. M. Bukatina; G. V. Kutekhova (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2018)
The article is devoted to the problems of safety of non-steroidal anti-inflammatory drugs. The analysis of 3,963 spontaneous reports to the Russian database for the period from December 7, 2008 to August 31, 2017, with the aim of identifying information on adverse reactions that have occurred during the application of NSAIDs is presented. Most often unwanted reactions were registered for preparations of acetylsalicylic acid, diclofenac, ibuprofen, ketorolac. A total of 6,257 adverse reactions were recorded. The greatest specific weight among all cases of undesirable reactions were disorders of the immune system, skin, subcutaneous tissues and gastrointestinal tract. The lack of therapeutic effectiveness of drugs was recorded in 280 cases. Most often, such ADR on NSAIDs were angioedema, urticaria, erosive gastritis, skin rash, increased blood pressure. In case of using of the over-the-counter drugs and self-medication it is necessary to work with the population to form a responsible attitude to the use of medicines, warn of possible complications of self-medication and conditions requiring compulsory medical attention.